Velocity Perception: Collision Handling Technique for Agent Avoidance Behavior - Nazreen Abdullasim; Ahmad Hoirul Basori; Md Sah Hj Salam; Abdullah Bade (Institute of Advanced Engineering and Science, 2013)
Collision avoidance behavior is always about maintaining free collision between virtual objects. It is also about generating evasion routing for the agents in virtual environment such as in crowd simulation. It consists of three processes which are construction of Field of Vision, Collision handling and collision response. Constructing field of vision is always a daunting task and always in enigma for the designer because it is subjected towards agent’s perception which is varies to each of them. There are few attempts on designing field of vision based on the agent’s dynamic focus toward its surrounding. Therefore, we present a top down approach study from crowd simulation modeling until the collision handling level in order to identify the suitable crowd modeling for our approach. Hence, at the end of this paper we will be able to discuss the possible techniques for constructing agent’s field of vision and analyze its potential in crowd simulation environment. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2599